Job Satisfaction of Employees in Information Technology Industry-A Study in Chennai City (International Journal of Psychosocial Rehabilitation, 2020)
Job satisfaction deals with the employee’s perception of anticipated and recognized work situations in an organization. This will enhance employee confidence, which improves morale and provides a better and more positive workplace, increases productivity, and builds commitment to the industry. The important theories like Maslow’s theory, Lawler’s theory, discrepancy theory, Edwin A. Locke’s range of affect theory, Taylor’s classical approach, human interactions theory, etc., analyze job satisfaction. It is noted that job satisfaction is related to the total relationship between an individual and the employer for which he is paid. The Chennai City was purposively chosen for this research work, and a total of 100 respondents working in the IT/ITES/BPO industry were contacted by using the random sample method with a pre-tested questionnaire. This study analyses about sex education, service tenure, experience, monthly income, opportunity for career growth, job security, relationships with co-workers, most congenial atmosphere, problems of the employees, inadequate time to complete work, possibility of growth, work-life balance, stress from superiors, satisfied with the overall compensation, job security, and the ability to use their skills. Sample Employees of IT Industries in Chennai City.